PELATIHAN PENGGUNAAN TEKNOLOGI DIGITAL DALAM PEMBELAJARAN STEM (SCIENCE, TECHNOLOGY, ENGINEERING, and MATHEMATICS) GUNA PEMBERDAYAAN GURU SEKOLAH DASAR - Tiatri, Sri; Jap, Tji Beng; Ie, Mei; Oeyta, Vienchenzia; Anisa Husnul Khotimah; Ayesha Desfitrianie; Margareta; Shalsa Dea Purnama; Zahra Shafira; Tasya Mulia Salsabila; Rahmiyana Nurkholizah (Jurnal Bakti Masyarakat Indonesia, 2024)
The 21st century learning that emphasizes the importance of integrating technology in education. The use of digital technology in STEM learning is an innovative way to increase student engagement and strengthen their understanding of the material. Digital technology and classroom management training was given to 51 elementary school teachers in Ciherang on September 4 2024. This training was carried out by providing a pretest, material, roleplay and posttest. The results of this activity can be seen from the pretest and posttest which show that the use of digital health tools increased by 45%, while classroom management skills increased by 19%. These results show the effectiveness of training in increasing teacher competence in these two aspects. However, obstacles are found among older teachers, who tend to be less motivated to learn digital technology. On the other hand, younger teachers who are more adept at technology can help their colleagues who are struggling. To overcome this challenge, it is recommended to conduct more in-depth follow-up training, especially regarding the application of digital technology in learning and school administration. Apart from that, mentoring for senior teachers is very important so that they can more easily adapt to technological developments. Collaboration between young and senior teachers needs to continue to be encouraged to increase technology adoption and the quality of education. This training not only improves teachers' technical skills, but also builds their confidence in managing classes using technology. ABSTRAK Pembelajaran abad 21 yang menekankan pentingnya integrasi teknologi dalam pendidikan. Penggunaan teknologi digital dalam pembelajaran STEM merupakan salah satu cara yang inovatif untuk meningkatkan keterlibatan siswa dan memperkuat pemahaman mereka terhadap materi. Pelatihan teknologi digital dan manajemen kelas yang diberikan kepada 51 guru SD di Ciherang pada 4 September 2024. Pelatihan ini dilakukan dengan memberikan pretest, materi, roleplay, dan posttest. Hasil dari kegiatan ini terlihat dari pretest dan posttest yang menunjukkan hasil penggunaan alat kesehatan digital meningkat sebesar 45%, sementara keterampilan manajemen kelas meningkat sebesar 19%. Hasil ini menunjukkan efektivitas pelatihan dalam meningkatkan kompetensi guru di kedua aspek tersebut. Namun, kendala ditemukan pada guru yang lebih tua, yang cenderung kurang termotivasi untuk mempelajari teknologi digital. Di sisi lain, guru muda yang lebih mahir dalam teknologi dapat membantu rekan-rekan mereka yang kesulitan. Untuk mengatasi tantangan ini, disarankan mengadakan pelatihan lanjutan yang lebih mendalam, khususnya terkait penerapan teknologi digital dalam pembelajaran dan administrasi sekolah. Selain itu, pendampingan bagi guru senior sangat penting agar mereka lebih mudah beradaptasi dengan perkembangan teknologi. Kerja sama antara guru muda dan senior perlu terus didorong untuk meningkatkan adopsi teknologi dan kualitas pendidikan. Pelatihan ini tidak hanya meningkatkan keterampilan teknis guru, tetapi juga membangun kepercayaan diri mereka dalam mengelola kelas yang menggunakan teknologi